PENGARUH KECEMASAN BERKOMPUTER DAN KEPRIBADIAN TERHADAP KINERJA AKUNTAN - Kushariyadi, Dedy (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This Study is aimed to examine the effect of computer anxiety and big fivepersonality on the performance of accounting educators. This model is tested on73 accounting educators at universities in Surabaya. Primary data were obtaineddirectly, through the distribution of questionnaires. Testing is done in two steps,first is multiple linear regression analysis and the second is hypothesis testing.The results of the analysis of the data from this study show that:(1) Computer anxiety had not effect on the performance of accounting educators.(2) Big five personality is influential on the performance of accounting educators.Keyword: Computer Anxiety, Big Five Personality, Performance of AccountingEducators.